2017
DOI: 10.15835/nbha45210867
|View full text |Cite
|
Sign up to set email alerts
|

Organic Agriculture and Innovative Crops under Mediterranean Conditions

Abstract: Climate change is the greatest environmental threat facing humanity worldwide. Areas of South-East Europe and Mediterranean basin are expected to be among the most vulnerable countries to climate change. As a result of climate change, new species and crops have been introduced and may be introduced in the coming years. In addition, FAO considers that Organic Agriculture is an effective mitigation strategy to climate change and can build robust soils that adapt better to weather extremes associated with climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…The identification of vulnerable areas and sectors and assessments of needs and opportunities for changing crops and varieties are valuable responses to climate change trends [ 25 ]. As a consequence of climate change, new climate-proof crops and cultivars should be introduced and tested, which should be able to provide food security, with improved stress tolerance, selecting promising varieties of cereals, grain legumes, and new crops may be introduced in the coming years [ 72 , 83 ]. According to [ 72 ] based on an assessment of the farming systems, new varieties and species with improved tolerance to drought and salinity were introduced in the crop rotations of rainfed and irrigated farming systems.…”
Section: Adaptation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of vulnerable areas and sectors and assessments of needs and opportunities for changing crops and varieties are valuable responses to climate change trends [ 25 ]. As a consequence of climate change, new climate-proof crops and cultivars should be introduced and tested, which should be able to provide food security, with improved stress tolerance, selecting promising varieties of cereals, grain legumes, and new crops may be introduced in the coming years [ 72 , 83 ]. According to [ 72 ] based on an assessment of the farming systems, new varieties and species with improved tolerance to drought and salinity were introduced in the crop rotations of rainfed and irrigated farming systems.…”
Section: Adaptation Strategiesmentioning
confidence: 99%
“…Furthermore, the new crops to be cultivated in the Mediterranean region are quinoa ( Chenopodium quinoa ) and amaranth [ 25 , 72 ]. Quinoa has a significant potential for increased production as a new cultivated crop in the Mediterranean region and other areas of the world including North America, Europe, and Asia, also the cultures bean, chickpea, lentil, nigella, camelina, chia, and linseed show potential interest in the yield in the Mediterranean [ 25 , 72 , 83 ]. This shows that innovative crops, well adapted to the future warmer and dryer Mediterranean region, can be viable alternatives to current crops [ 25 ].…”
Section: Adaptation Strategiesmentioning
confidence: 99%
“…In Poland and Ukraine, winter camelina cultivars were traditionally cultivated (Kurasiak-Popowska et al 2018) since that area was identified as one of the camelina centers of origin. The undisputable agronomic plasticity of camelina has more recently attracted the attention of scientists and growers since it is one of the unique European crops able to fit easily into diverse cropping systems, both under conventional and organic farming (Bilalis et al 2017;Royo-Esnal and Valencia-Gredilla 2018). One of the winning features of camelina remains its full adaptability to available agricultural equipment on farms (Sindelar et al 2017), which is often identified as a major barrier for the feasible development of a new crop.…”
Section: Sustainable Cultivation Strategies For Europementioning
confidence: 99%
“…On one hand, one solution to adapt to climate change is to introduce new crops in new climate zones as the climatic situations are changing rapidly. Some examples are shown to be already possible in the Mediterranean area (Bilalis et al, 2017). On the other hand, the existing agricultural practices should be reconsidered so that agriculture could be a very important key to mitigate the production of greenhouse gases but also to absorb permanently greenhouse gases from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%